THE ROLE OF FAMILY ECONOMIC EDUCATION IN ISLAMIC PERSPECTIVE - Yani Nuraeni; Dini Nurdiani (International Journal of Accounting, Finance and Business, 2023)
Economic Education is closely related to Islam Because Islam as a Religion covers all aspects. Namely, it contains folk economics literature inspired by Islamic values. Understanding the importance of the values of economic education must begin to be upheld on a family scale as early as possible. This study discusses the role of economic education in the family from an Islamic perspective. This research is library research or library research, which relies on sources on library materials. The results of this study are the role of economic education related to aspects of education in the family. The family must apply habits such as saving, being thrifty, and being selective in purchasing goods and services. This habituation will form a mindset that is manifested in economic education literacy. The role of economic education is related to religious aspects in the family, namely the father or mother introduces Islamic economics education to their family members, which is close to religious nuances such as teaching that Islam requires that every human activity is not only worldly (material) value, but should also have spiritual value. The role of economics education is related to aspects of faith in the family, namely so that there is a belief that the universe is (provided) for the benefit of humans so that it has implications for several good things related to the use of the economy solely for broad benefits..